The New World species of Cerodontha (Xenophytomyza) Frey (Diptera: Agromyzidae) - Boucher, Stéphanie (Zootaxa, 2003)
The New World species of the subgenus Cerodontha (Xenophytomyza) Frey are reviewed. There are two species in the region: C. (X.) biseta (Hendel) (western Palearctic, eastern Nearctic, Jamaica); and C. (X.) illinoensis (Malloch) (eastern Nearctic). Both species are illustrated and a key is provided to distinguish the species. Cerodontha (Xenophytomyza) biseta was apparently introduced recently to the eastern Nearctic and several new locality records in eastern Canada and northeastern United States are noted here; the record of C. (X.) biseta from Jamaica represents the first record of the subgenus from the Neotropical region.